Penggunaan Adsorben Karbon Aktif Bambu Kuning (Bambusa Vulgaris Var. Striata) dan Bentonit dalam Proses Pengolahan Limbah Cair Laboratorium Kimia Politeknik Negeri Cilacap - Putri Novitasari; Fadhilah Yumna Hanifah (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Cilacap State Polytechnic chemical laboratory has waste derived from the disposal of practicum and testing activities that use hazardous and toxic materials or chemicals. Adsorption process with the addition of preparation bentonite and bamboo charcoal with bambusa vulgaris var type. striata or yellow bamboo. Activation of bamboo (Bambusa vulgaris var. striata) chemically using a solution of 10% H3PO4 (phosphoric acid). Chemical activation of bentonite by mixing bentonite with a 5% HCl solution. This study aims to find out the decrease in concentrations of Total Dissolved Solid (TDS) and Total Suspended Solid (TSS) in the liquid waste treatment of Cilacap State Polytechnic chemical laborator. Chemical activation of adsorbents decreased the concentration level of Total Dissolved Solid (TDS) by 88.793% and decreased concentration of Total Suspended Solid (TSS) by 84%. The trapping capacity of yellow bamboo adsorben material (Bambusa vulgaris var. striata) with 10% H3PO4 chemical activation and bentonite with 5% HCl chemical activation can trap total dissolved solid (TDS) adsorent capacity levels of 6,866 mg/g and Total Suspended Solid (TSS) absorption capacity of 0.0875 mg/g. Utilization of bentonite and yellow bamboo waste (Bambusa vulgaris var. striata) can be used as an effective adsorbent material in the processing of chemical laboratory liquid waste.